Competências socioemocionais e as práticas de psicólogas (os) escolares/educacionais no estado do Ceará: possíveis (des)articulações - Pereira, Luisa Carolina Holanda (2022)
Socio-emotional skills have been highlighted in the productions of researchers and scholars of education and educational psychology in recent years, as one of the reflections of the paths that the school has taken in the face of the demands of social and economic transformations. Socio-emotional skills, according to the Ayrton Senna Institute (IAS) and the Organization for Economic Cooperation and Development (OECD) are skills that, integrated with cognitive knowledge, help form committed, motivated, solidary, socially responsible and productive citizens. These concepts are used in the current National Common Curricular Base (BNCC), a document formulated to guide school curricula and guarantee the essential learning that students must have throughout Basic Education. Ceará is one of the pioneers in the implementation of socio-emotional skills in public and private schools, where psychologists are often the ones who operationalize this articulation to offer students these ideas. We observe, therefore, how the new orders and logics of the school are articulated and how these documents seem to emphasize a neoliberal logic, its role in preparing for life and the labor market, which requires that its workers are also trained based on the requirements socioemotional. The objective of the research is to problematize the articulation of socio-emotional skills and the professional practices of Psychologists, based on reports of work experiences in public and private schools/educational institutions in Ceará. The methodological theoretical contribution of cartographic research presupposes a plan of genealogical inspiration, therefore, it is, on the one hand, centered on a bibliographical analysis (articles, documents) of the conditions of possibility for the emergence of a discursivity about socio-emotional competences and their relationship with the field psi. And on the other, an experience plan through the application of a form and interviews with Psychology professionals working in public or private education in Ceará. The online form was answered by 27 participants, where we then conducted 4 cartographic management interviews with professionals who reported using socio-emotional skills in their practices in schools in the form. Thus, the research showed us how the construction of the performance of Psychology professionals has been influenced by the models and methodologies of neoliberal institutes and that makes it necessary to think about the importance of the debate about what is being demanded of Psychology in the educational context in its relationship with the demands of neoliberal capitalism.